JUVENILE DELINQUENCY (KENAKALAN REMAJA) DALAM SUDUT PANDANG PSIKOLOGI DAN HUKUM - Tita Rosita; Yulia Nur Annisa; Manayra Aisha Putri Indradjaja; Aninda Nurbaeti Rahman (IKIP Siliwangi, 2023)
This study aims to examine juvenile delinquency from a psychological and legal perspective. The research method used is qualitative research with a literature study approach. Based on the results of the literature study, it was found that juvenile delinquency from a psychological perspective is a form of adolescent behavior that leads to social pathological symptoms caused by permissive parenting, lack of family affection and communication, and the role of peer groups. Meanwhile, according to the legal point of view, juvenile delinquency is a form of unlawful behavior committed by adolescents under the age of 18 and handling it is regulated by the Child Protection Act and the Juvenile Justice Act.